Statistical Yearbook for Latin America and the Caribbean 2023 - Economic Commission for Latin America; the Caribbean (United Nations, 2024)
The Statistical Yearbook for Latin America and the Caribbean of ECLAC presents a set of basic statistics on the economic, sociodemographic and environmental situation of the region during a specific time period. This edition of the Yearbook includes information available up to mid-December 2023. The Yearbook comprises three chapters. The first covers demographic and social indicators and includes statistical information on population, labour, education, health, housing and basic services, poverty and income distribution, and gender. The second chapter presents economic statistics relating to trade, balance of payments and domestic prices, as well as national accounts. The statistical series are expressed in dollars. The third chapter provides quantitative information available on the environment referring to physical characteristics, land cover, biodiversity, environmental quality, energy, biological and water resources, emissions, extreme natural events and disasters, environmental regulations and governance, and human settlements. Given the abundance of data —often diverse and sometimes conflicting— now accessible to researchers, special attention must be paid to technical aspects specifying the source of the data, their definition and coverage. This information is presented in a fourth chapter available in the digital version of this Yearbook, which deals with methodology and metadata, supplementing the more specific information contained in the footnotes and sources of each of the tables and graphics in this Yearbook.